2009
DOI: 10.1186/1743-422x-6-49
|View full text |Cite
|
Sign up to set email alerts
|

Profile of time-dependent VEGF upregulation in human pulmonary endothelial cells, HPMEC-ST1.6R infected with DENV-1, -2, -3, and -4 viruses

Abstract: In this study, the upregulated expression level of vascular endothelial growth factor (VEGF) in a pulmonary endothelial cell line (HPMEC-ST1.6R) infected with dengue virus serotypes 1, 2, 3, and 4 (DENV-1, -2, -3 and -4), was investigated. This cell line exhibits the major constitutive and inducible endothelial cell characteristics, as well as angiogenic response. Infection by all four DENV serotypes was confirmed by an observed cytopathic effect (CPE), as well as RT-PCR (reversetranscription polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…2 and 3, which indicate that IFN secreted by a small percentage of initially infected cells protects surrounding ECs from dengue virus spread. Some dengue virus-induced EC responses were also analyzed in LSEC-1, HMEC-1, or HPMEC-ST1.6R cell lines (9,10,41,63). Dengue virus infection of the HPMEC-ST1.6R cell line increased IL-6 and IL-8 (6 to 8 days pi) as well as vascular endothelial cell growth factor (VEGF) levels (9,10).…”
Section: Fig 2 Ifn-␤ Restricts Dengue Virus Spread Within Ecs (A) Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3, which indicate that IFN secreted by a small percentage of initially infected cells protects surrounding ECs from dengue virus spread. Some dengue virus-induced EC responses were also analyzed in LSEC-1, HMEC-1, or HPMEC-ST1.6R cell lines (9,10,41,63). Dengue virus infection of the HPMEC-ST1.6R cell line increased IL-6 and IL-8 (6 to 8 days pi) as well as vascular endothelial cell growth factor (VEGF) levels (9,10).…”
Section: Fig 2 Ifn-␤ Restricts Dengue Virus Spread Within Ecs (A) Ecmentioning
confidence: 99%
“…Some dengue virus-induced EC responses were also analyzed in LSEC-1, HMEC-1, or HPMEC-ST1.6R cell lines (9,10,41,63). Dengue virus infection of the HPMEC-ST1.6R cell line increased IL-6 and IL-8 (6 to 8 days pi) as well as vascular endothelial cell growth factor (VEGF) levels (9,10). In contrast, we found no induction of capillary permeabilizing VEGF (9,23) in primary human ECs, and 1 to 2 days after infection we detected IL-6 and IL-8 induction.…”
Section: Fig 2 Ifn-␤ Restricts Dengue Virus Spread Within Ecs (A) Ecmentioning
confidence: 99%
“…DENV infection of ECs has been proposed to contribute to this pathophysiology; however, the mechanism by which infected ECs modulate vascular (12,28,29), which is reported to be a bladder carcinoma rather than endothelial in nature (30). In addition, ECs from different tissue origins, such as LSEC-1, HMEC-1, or HPMEC-ST1.6R, which may have different characteristics, responded differently to DENV infection (9,15,31,32). In the present study, primary HUVECs isolated from normal human umbilical vein were evaluated because they are more relevant to the pathophysiology of DHF/DSS and the most commonly used model to investigate macromolecule transport (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of dengue, it has been demonstrated that dengue virus could down-regulate the secretion of sVEGFR-2 by endothelial cells, thus promoting an increase in microvascular permeability via excess of circulating VEGF-A [15,16]. Indeed, clinical studies have demonstrated that patients with DHF may present high levels of VEGF-A [17] and low levels of sVEGFR-2 [15,18].…”
Section: Discussionmentioning
confidence: 99%